Mothers' Knowledge about Feeding Children Aged 6-24 Months - Erniawati Pujiningsih; Herni Sulastien; Musniati Musniati; Siti Aisyah; Dahliana Isnaini (Indonesian Journal of Global Health Research, 2024)
Proper provision of complementary foods starting from the age of 6-24 months and continuing breastfeeding until the age of 2 years must be optimized by increasing maternal knowledge. This is because mothers have an important role in the growth and development of children, especially maternal knowledge has an influence on the mindset and level of concern to provide the right food intake for their children. The purpose of this study was to identify the characteristics of respondents based on age, education and occupation. Identify mother's knowledge about complementary feeding for children aged 6-24 months in Giri Madia village. This study used descriptive method. The sample size was 44 people with sampling using simple random sampling technique. Data collection using a questionnaire, where the questionnaire has been used during preliminary studies by showing very good results, namely 6 out of 10 respondents said that complementary foods should be given at the age of 6 months. Respondents were asked to select one of the available answers by ticking, namely: true or false. Data processing was carried out with several stages, namely editing, coding, tabulating, and cleaning. The results showed that the characteristics of respondents based on age were mostly early adulthood as many as 23 respondents (52%), education almost half had a junior high school education as many as 21 respondents (47.7%), the occupation of almost all respondents was working.